The image and the brazen serpent: division, mediation and the translatability of cultures - De Villiers-Human, Suzanne (University of the Free State, 2010)
This article confronts possible effects of the crisis of intercultural communication by investigating the transforming power of images to reorient or transfigure accepted cultural meanings. With current image theorists such as W J T Mitchell and Hans Belting it emphasises that the image’s power to self-create or to possess a life, presence or soul of its own – that aspect of the image that makes it seem animated and able to trap or immerse – is not merely a relic of ritual, cultic or idolatrous comprehensions, but may rather be one of the constant features in ontologies of the image.

Hierdie artikel neem die moontlike gevolge van die krisis van inter-kulturele kommunikasie onder die loep, deur die transformerende mag van beelde om aanvaarde kulturele betekenisse te herorïenteer of te transfigureer, te ondersoek. Tesame met hedendaagse beeldteoretici soos W J T Mitchell en Hans Belting beklemtoon dit dat die beeld se selfskeppende mag of die skynbare vaardigheid daarvan om ’n eie lewe, teenwoordigheid of siel te besit – daardie aspek van die fassinerende beeld wat dit skynbaar lewendig maak – nie bloot ’n oorblyfsel van rituele of kultiese ervarings is nie, maar dat dit eerder een van die konstante eienskappe in ontologieë van die beeld is.
Keywords: Intercultural communication; Images; Mitchell, W. J. T.; Belting, Hans